Makna Seksualitas dalam Naskah Sastra Pesantren - Muhammad Abdullah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The study of “Uqudullujjain Fi Huqquq Azzaujain” text shows that there is strong gender bias and sexual in the discourse of pesantren literature. It can be seen, among others, from the domestication of women in household. For example, women are suggested to work at home (doing things around the well, bedroom, and kitchen). Women are supposed to be housewives, and so they are prohibited to work outside their home, and they are given limited access to go outside. However, time has changed gender perspective. Nowadays there has been development of new advances occurring among pesantren leaders. For example, there are many Muslim women who work in economic or politic sectors as mass leaders, regents, mayors and district or village heads. This certainly shows interesting opportunities for women to be equal to men. Therefore, in the future, women will be able to be more independent, strong, and even they can obtain good achievements.